Crystallization of the C‐terminal domain of the fibre protein from snake adenovirus 1, an atadenovirus. Issue 12 (1st December 2013) - Singh, Abhimanyu K.; Menéndez‐Conejero, Rosa; San Martín, Carmen; van Raaij, Mark J.
<x xml:space="preserve">Abstract</x> Adenovirus fibre proteins play an important role in determining viral tropism. The C‐terminal domain of the fibre protein from snake adenovirus type 1, a member of the Atadenovirus genus, has been expressed, purified and crystallized. Crystals were obtained belonging to space groups P212121 (two different forms), I213 and F23. The best of these diffracted synchrotron radiation to a resolution of 1.4 Å. As the protein lacks methionines or cysteines, site‐directed mutagenesis was performed to change two leucine residues to methionines. Crystals of selenomethionine‐derivatized crystals of the I213 form were also obtained and a multi‐wavelength anomalous dispersion data set was collected.